Longitudinal Risk Phenotyping in Incident Systemic Sclerosis-associated Pulmonary Arterial Hypertension (SSc-PAH): An Unsupervised Cluster Analysis of the PHAROS Registry - Friedman, Samuel H; Williams, Jacob; Hyer, Madison; Fox, Nicholas; Ramakrishnan, Viswanathan; Lammi, Matthew R; Steen, Virginia D; Argula, Rahul G (Journal of Pulmonology and Respiratory Research, 2024)
Background: Systemic sclerosis-associated pulmonary arterial hypertension (SSc-PAH) is characterized by pulmonary arterial remodeling resulting in right ventricular failure and death if untreated. Despite therapeutic advances, there is survival variability within the SSc-PAH population. The aim of this study was to delineate high-risk subgroups of SSc-PAH using readily available clinical parameters. Methods: We analyzed data from the PHAROS database, a prospective observational registry of incident SSc-PAH patients. Latent class modeling was performed based on trends in 6MWD over time. We compared survival between the clusters regarding baseline clinical parameters and changes in these parameters over time. Results: We identified four unique groups within 103 patients meeting our inclusion criteria, based on trajectories of 6MWD. Patients in Cluster 4 exhibited a decline in 6MWD over time and had the worst prognosis with a median survival of 3 years. Patients in Cluster 3, with the lowest baseline 6MWD, were associated with lower median survival (5 years) when compared to Clusters 1 and 2 (> 9 and 7 years, respectively), despite an improvement in 6MWD over time. There were no meaningful changes in SF-36 and WHO functional class between the clusters, but BNP trended higher over time in the higher-risk clusters. Conclusion: We identified high-risk subsets of SSc-PAH characterized by significantly worse survival. Incident SSc-PAH patients with a decline in 6MWD over time or low baseline 6MWD had worse survival when compared to SSc-PAH patients who demonstrated relatively stable or mild reduction in 6MWD over time.